2:17 Newton E. Winn Residence - Unknown (publisher not identified, 1897)
Newt Winn, 1897 graduate of Kirksville Mercantile College and newly hired bookkeeper for the John Storm Axe Handle Company, is pictured with his sisters Minnie and Lucy on the front porch of their family home. Newt left Storm's in 1900 and for the next twenty years was associated with Kirksville Savings Bank, first as bookkeeper, then as assistant cashier. This home was located on South First Street at the city limits.